Research on the loss characteristics of high-voltage cascaded energy storage systems based on IGCTs - Chen, Yushuo; Qu, Lu; Yu, Zhanqing; Zhao, Biao; Kang, Qian; Cui, Kangsheng; Zeng, Rong (Frontiers in Energy Research, 2023)
High-voltage cascaded energy storage systems have become a major technical direction for the development of large-scale energy storage systems due to the advantages of large unit capacity, high overall efficiency, satisfactory economy, reliable safety, and easy access to grid dispatching. The loss characteristics analysis is the design basis of the water-cooling system of a high-voltage cascaded energy storage system, and its accurate calculation can determine the system's safe and reliable operation of the system. This paper first introduces the four-quadrant operation principles of a cascaded H-bridge energy storage system, and analyzes the calculation method of the loss of the Integrated Gate-Commutated Thyristor (IGCT) based power module; On this basis, it studies the loss characteristics of the cascaded energy storage system and analyzes the influence of different modulation strategies and third harmonic injection on the loss characteristics of the energy storage system; Finally, this paper has completed the loss test for the engineering prototype module and compared the test results with theoretical calculation results to verify the accuracy of the loss calculation method of the high-voltage cascaded energy storage system.